Developing Teaching Material “Jurus Kilat! 6 Minggu Mahir Membaca Tanpa Eja” To Solve Initial Reading Difficulties in Primary School (Al-Aulad: Journal of Islamic Primary Education, 2023)
The purpose of this study is to determine the development, validity, effectiveness, and attractiveness of teaching material "Jurus Kilat! 6 Minggu Mahir Membaca Tanpa Eja" to overcome initial reading difficulties in primary school. This study used the ADDIE model. The developed teaching material are validated by material experts and teaching material experts. The implementation of teaching material is designed with stages of small-scale trials, large-scale trials, teacher and student response questionnaires. The subjects of this research are the Ist grade students of MI Ma'arif NU Sungegeneng, totalling 28 students. Data collection by observation, interview, questionnaires, pre-test and post-test questions, and documentations. The results of the validity test of teaching material by material experts obtained a percentage of 92.9 and by teaching material experts of 96.7%. The results of the effectiveness test of teaching material seen from the pre-test and post-test values by conducting the N-Gain test using the SPSS 29.0 application obtained an average of 0.56. The results of the attractiveness test of teaching material seen from the teacher response questionnaire obtained a percentage of 95% and the student response questionnaire obtained a percentage of 97.4% which emphasized that teaching material is very suitable to be used as learning support.Keywords: Beginning Reading, Reading Difficulties, Teaching Materials